The Vaccine Communication Demands on Community-Based Workforces - Rauh, Lauren; Patry, Dave; Zambrano, Michelle; Lathan, Hannah Stuart; Tavarez, Emilio; El-Mohandes, Ayman (Frontiers in Public Health, 2022)
Community-based organizations (CBOs) are experiencing some of the highest demand in years for a wide spectrum of health and social services. Their client-facing employees have taken on a new and challenging role–they are a sought-after source of COVID-19 vaccine information and guidance. These health and social service workforces operating on the frontlines do their best to meet the increased need for services and information, often without additional resources or training to do so. The most effective immediate response to this challenge is a comprehensive communication support system working in tandem with CBOs. Our three organizations, the New York Vaccine Literacy Campaign at the CUNY Graduate School of Public Health and Health Policy, Hunger Free NYC, and Health Leads, have collaborated in key short-term approaches to meet these needs. We outline these processes and anticipated outcomes and offer lessons learned to advocate for long-term structural changes needed to increase community-level communication support.